Intermittency and Passive Scalar Nature of Electron Density Fluctuations in the High‐Latitude Ionosphere at Swarm Altitude. Issue 18 (21st September 2020) - Consolini, G.; De Michelis, P.; Alberti, T.; Coco, I.; Giannattasio, F.; Tozzi, R.; Carbone, V.
Abstract: Some physical processes due to Sun‐Earth interaction can influence the configuration and the dynamics of the high‐latitude ionospheric plasma, particularly during geomagnetically disturbed periods. A possible consequence of this interaction is the occurrence of turbulent fluctuations that can be observed both in magnetic and electric fields and plasma density. Here, we focus on the intermittent nature of high‐latitude ionospheric electron density fluctuations during geomagnetically disturbed periods as observed by one of the satellites of the ESA‐Swarm constellation. The most obvious finding emerging from this study is the strong intermittent character of electron density fluctuations and the existence of an agreement between the anomalous scaling features of electron density fluctuations and those expected from a passive scalar quantity in fluid turbulence. This latter result supports the view of a passive scalar behavior of electron density in the high‐latitude ionosphere that can have significant implications in the field of Space Weather studies. Plain Language Summary: Turbulence phenomena represent a key element for understanding the ionospheric dynamics and have a great impact on the features of both magnetic and electric fields and plasma density. It has been suggested that turbulence can be one of the mechanisms responsible for the generation of ionospheric irregularities, which may strongly affect the satellite navigation, positioning, and communication systems. In such a framework the characterization of turbulent fluctuations of ionospheric plasma parameters paves the way for a better modeling of space weather related phenomena. The ESA‐Swarm mission provides a unique opportunity to investigate the relevance of turbulence phenomena in the topside ionosphere. Using data recorded on board Swarm A satellite at high latitudes, the intermittent and passive scalar features of electron density fluctuations are investigated. The obtained results support the idea that plasma density irregularities exhibit a complex dynamic behavior similar to that of a turbulent field. Turbulence is therefore confirmed as a fundamental element to be taken into account in order to fully understand the occurrence of large local electron density gradients. Key Points: The ionospheric electron density fluctuations show an intermittent and passive scalar behavior Plasma irregularities exhibit a complex dynamic behavior similar to a turbulent velocity field Turbulence is a key point to understand the occurrence of large local electron density gradients